Clinical Management of Suppurative Osteomyelitis, Bisphosphonate-Related Osteonecrosis, and Osteoradionecrosis: Report of Three Cases and Review of the Literature - Eduardo Pereira Guimarães; Fernanda Rafaelly de Oliveira Pedreira; Bruno Correia Jham; Marina Lara de Carli; Alessandro Antônio Costa Pereira; João Adolfo Costa Hanemann (Hindawi Limited, 2013)
In the past, osteomyelitis was frequent and characterized by a prolonged course, treatment response uncertainty, and occasional disfigurement. Today, the disease is less common; it is believed that the decline in prevalence may be attributed to increased availability of antibiotics and improvement of overall health patterns. Currently, more common osteomyelitis variants are seen, namely, osteoradionecrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ). Osteomyelitis, ORN, and BRONJ can present with similar symptoms, signs, and radiographic findings. However, each condition is a separate entity, with different treatment approaches. Thus, accurate diagnosis is essential for adequate management and improved patient prognosis. The aim of this paper is to report three cases of inflammatory lesions of the jaws-osteomyelitis, ORN, and BRONJ-and to discuss their etiology, clinical aspects, radiographic findings, histopathological features, treatment options, and preventive measures.